Bladder irrigation with tap water to reduce antibiotic treatment for catheter-associated urinary tract infections: an evaluation of clinical practice - van Veen, Felice E. E.; Den Hoedt, Stefan; Coolen, Rosa L.; Boekhorst, Jessica; Scheepe, Jeroen R.; Blok, Bertil F. M. (Frontiers in Urology, 2023)
Introduction: Catheter-associated urinary tract infection (CAUTI) is a common complication among patients with urinary catheters and is often treated with antibiotics. With increasing rates of antibiotic resistance, it is necessary to explore alternative treatment options for CAUTIs. The aims of this study were 1) to assess the efficacy and treatment satisfaction of bladder irrigation (BI) with tap water to prevent and treat CAUTIs, 2) and to evaluate the current use of BI for CAUTIs among Dutch clinicians. Methods: The first part of this study consisted of a cross-sectional study among patients with intermittent or indwelling catheters who performed BI with tap water between March 2020 and May 2021. Efficacy, treatment satisfaction, and Patient Global Impression of Improvement (PGI-I) were assessed using questionnaires. Outcomes were compared between neurogenic lower urinary tract dysfunction (NLUTD) and non-NLUTD patients. Factors associated with overall treatment satisfaction were determined using logistic regression analysis. Second, a nationwide survey of Dutch clinicians was conducted to evaluate the current use of BI for CAUTIs. Results: A total of 99 patients who were performing BI for at least three months were included. The median age was 61.9 years, 41.4% had NLUTD, and 72.2% performed BI >1 year. The majority of NLUTD (65.9%) and non-NLUTD patients (68.4%) were (very) satisfied with BI. Women had higher odds of reporting higher satisfaction and each additional CAUTI decreased the odds. Most NLUTD (85.4%) and non-NLUTD (65.5%) patients reported improvement on the PGI-I with a difference in favour of NLUTD patients (p=0.002). Additionally, 40.4% of the patients had no CAUTI, and 59.6% reported 1.39 (SD 2.06) CAUTIs. Only half of these self-reported CAUTIs were treated with antibiotics. In addition, 33 (58.9%) clinicians used BI for CAUTIs, of which ten used tap water as irrigation agent. Discussion: This study provides first evidence supporting the efficacy of BI with tap water in the treatment of CAUTIs and reducing the use of antibiotics. Patients are overall satisfied and experience improvement in their condition with BI. In addition, the majority of the surveyed Dutch clinicians use BI for CAUTIs. However, irrigation with tap water is still not widely used.